Hubungan antara Father Love Absence dengan Self-Control pada Siswa - Sarah Febrela Tobing; Sri Putri Rahayu (Batanang : Jurnal Psikologi, 2026)
This study aimed to examine the relationship between father love absence and self-control among students of MTSN 3 Tanah Datar. The research was motivated by the phenomenon of low self-control in some adolescents, characterized by impulsive behavior, difficulty regulating emotions, and rule violations. The lack of paternal affection and involvement is presumed to be one of the factors influencing adolescents’ self-control development. This study employed a quantitative correlational approach with a sample of 80 students selected through proportionate stratified random sampling. Data were collected using the father love absence and self-control scales and analyzed using Spearman’s rho correlation test. The results revealed a significant negative relationship between father love absence and self-control (r = −0.348; p = 0.002; p < 0.01), with a weak correlation strength. Higher levels of father love absence were associated with lower levels of self-control. Overall, father love absence was categorized as high, while self-control was categorized as moderate.